Peran Self-regulation dalam Memoderasi Pengaruh Communication skill Terhadap Collaboration skill Mahasiswa - Ririen, Deci; Nurjayanti, Nurjayanti (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
One of the competencies or skills that human resources must have in order to compete in the global era is collaboration skills. This research aims to analyze the influence of communication skills and self-regulation on student collaboration skills. As well as analyzing the role of self-regulation as a moderating variable. The research subjects were 95 students of the Indragiri Institute of Technology and Business. Data collection instruments used interviews and a list of questions/questionnaires. The data analysis technique used in this research is quantitative data analysis and uses the Moderated Regression Analysis (MRA) model with the help of SmartPLS. The research results obtained are that there is an influence of communication skills on collaboration skills. There is an influence of self-regulation on collaboration skills and self-regulation moderates the influence of communication skills on collaboration skills.